Narrating Chinese Teaching and Learning in Culturally Local Thai Schools - Duangmanee, Katematu; Waluyo, Budi (Journal of Education Culture and Society, 2024)
Aim. Despite the popularity of Chinese foreign language teaching in schools worldwide, it is still little known how culturally local schools manage their Chinese teaching and learning. To address this gap, this study examined the pedagogical strategies and practices of Chinese as a Foreign Language (CFL) instruction in Thai secondary education, addressing the insufficient exploration of CFL educational undertakings beyond China's borders. Methods. A narrative inquiry approach with interviews was employed. The sample included 34 school principals (11.8% female, 88.2% male), whose insights shed light on the cardinal aspects of CFL instruction and learning. Results. The outcomes revealed essential elements shaping CFL pedagogy in culturally local schools in Thailand, including curricular considerations, collaboration through knowledge-sharing platforms and cultural events, teaching methodologies with teacher preparation and native-speaking instructors, learning activities inside and outside the classroom, and school-wide educational initiatives. Conclusion. Overall, the findings contribute to the understanding of CFL education in Thailand and offer potential avenues for future research and pedagogical enhancement.